Agent Orange and head and neck cancer: A systematic review and meta‐analysis - Neil P. Monaghan; Kelsey A. Duckett; Shaun A. Nguyen; Jason G. Newman; Alexandra E. Kejner; W. Greer Albergotti (World Journal of Otorhinolaryngology-Head and Neck Surgery)
Abstract Objective To assess the incidence of head and neck cancer in patients exposed to Agent Orange and related dioxins. Methods Studies were identified through CINAHL, PubMed, and Scopus. Primary studies were identified through April 2023. Articles were included reporting incidence of head and neck cancer and/or deaths due to head and neck cancer in participants exposed to Agent Orange. Meta‐analysis of proportions was conducted to calculate incidence and mortality by primary site in those who were exposed to Agent Orange and for control groups. A comparison of proportions was used to compare rates in exposed and control groups. Results Of 1530 unique abstracts screened, 13 studies were included in the systematic review. Of the exposed patients with reported subsites, oral cavity (31.2%), and larynx (14%) were the most common. Of the exposed patients with reported deaths and subsites, oropharynx (0.25%) was the most common primary site in patients who died. The most common subsites of those who were not exposed, oropharynx (0.13%), and larynx (0.16%). Head and neck cancer of all subsites was more common in those exposed to Agent Orange than in unexposed controls (difference 0.061%; 95% confidence interval: 0.04%–0.08%, p < 0.0001). Conclusions Our findings suggest that head and neck cancer is more common in those who were exposed to Agent Orange than those who were not. Additionally, individuals exposed to Agent Orange were more likely to die from head and neck cancer. Further investigation is warranted to evaluate subsite‐specific outcomes given the limitations of our study design.